National Evaluation of Safe Start Promising Approaches Assessing Program Outcomes - Jaycox, Lisa H. (RAND Corporation, 2011)
Safe Start Promising Approaches (SSPA) is the second phase of a community-based initiative focused on developing and fielding interventions to prevent and reduce the impact of children's exposure to violence. This report shares the results of SSPA, which was intended to implement and evaluate promising and evidence-based programs in 15 program sites across the country.